Caudal Approach to Laparoscopic Liver Resection—Conceptual Benefits for Repeated Multimodal Treatment for Hepatocellular Carcinoma and Extended Right Posterior Sectionectomy in the Left Lateral Position - Tomoyoshi Endo; Zenichi Morise; Hidetoshi Katsuno; Kenji Kikuchi; Kazuhiro Matsuo; Yukio Asano; Akihiko Horiguchi (Frontiers in Oncology, 2022)
We had reported the novel concept of “caudal approach in laparoscopic liver resection” in 2013. In the first report, the caudal approach of laparoscopic transection–first posterior sectionectomy without prior mobilization of the liver in the left lateral position was described. Thereafter, 10 complex laparoscopic extended posterior sectionectomies with combined resection of the right hepatic vein or diaphragm were performed using the same approach. In the present study, the short-term outcomes of these cases and 42 cases of laparoscopic sectionectomies or hemi-hepatectomies (excluding left lateral sectionectomy) were compared. There was no statistically significant difference between the groups in terms of patients’ backgrounds, diseases for resection, preoperative liver function, tumor number and size, as well as outcomes, operation time, intraoperative blood loss, morbidity, conversion to laparotomy, and post-operative hospital stay. Even complex laparoscopic extended posterior sectionectomy was safely performed using this procedure. This approach has the technical benefits of acquiring a well-opened transection plane between the resected liver fixed to the retroperitoneum and the residual liver sinking to the left with the force of gravity during parenchymal transection, and less bleeding from the right hepatic vein due to its higher position than the inferior vena cava. Furthermore, it has an oncological benefit similar to that of the anterior approach in open liver resection, even in posterior sectionectomy. The detailed procedure and general conceptual benefits of the caudal approach to laparoscopic liver resection for repeated multimodal treatment for hepatocellular carcinoma are described.